Treatment mode and prognosis of esophageal perforation after radiotherapy in patients with esophageal carcinoma - Chan-Jun, Zhen; Wen-Wen, Bai; Ping, Zhang; Yu-Zhi, Song; Ya-Jing, Wang; Xue-Ying, Qiao; Zhi-Guo, Zhou (Frontiers in Oncology, 2023)
Objective: Retrospectively analyzed the EC patients with EP after radiotherapy to discuss the treatment and prognosis. Methods: Data of patients with EC who had EP after radiotherapy in Hebei Cancer Hospital were collected from 2001 to 2020 and retrospectively analyzed. The inclusion criteria were as follows: 1.) pathologically confirmed esophageal squamous cancer, 2.) non-surgical treatment, such as treatment by radiotherapy with or without chemotherapy, 3.) no sign of EP before radiotherapy, 4.) confirmed EP after radiotherapy; 5.) without serious medical illness, with a KPS score > 70, and 6.) with no other types of cancer, except EC. Results: A total of 94 patients with EC were enrolled, among which 72 were males and 22 were females, with a median age of 62 (38–82) years. The tumor was located in the upper thoracic in 45 patients, middle thoracic in 45 patients, and lower thoracic in 4 patients. There were 30 cases of tracheoesophageal fistula (TEF) and 64 cases of esophagomediastinal fistula(EMF). All patients died within 11 months (median: two months) after EP. After EP, 48 patients were treated by tube feeding (include nasal feeding and gastrostomy), 26 patients by esophageal stenting, and 20 patients by fluid infusion therapy, and their one, three, and six months survival rates after EP were 81.3%, 31.3%, and 12.5% (P = 0.000). In the TEF group, the one, three, and six month survival rates after EP of tube feeding, esophageal stenting and fluid infusion groups were 88.2%, 17.6%, 11.8%; 45.5%, 27.3%, 0%; and 50.0%, 50.0%, 0% (P = 0.345). In the EMF group, the one, three, and six months survival rates after EP of this three groups were 77.4%, 38.7%, 12.9%; 26.7%, 20.0%, 6.7%; and 22.2%, 11.1%, 0% (P=0.002), respectively. Conclusion: Most patients with EP after radiotherapy died within six months, with low survival and poor prognosis. Tube feeding therapy can achieve relatively good survival, especially for patients with EMF. The survival of patients treated by tube feeding therapy is significantly better than the survival of those treated by other methods.